A Formidable Task: Reflections on obtaining legal empirical evidence on human trafficking in Canada - Millar, Hayli; O'Doherty, Tamara; Roots, Katrin (Anti-Trafficking Review, 2017)
This article explores the experiences, challenges and findings of two empirical research studies examining Canada’s legal efforts to combat human trafficking. The authors outline the methodologies of their respective studies and reflect on some of the difficulties they faced in obtaining empirical data on human trafficking court cases and legal proceedings. Ultimately, the authors found that Canadian trafficking case law developments are in their early stages with very few convictions, despite a growing number of police-reported charges. The authors assert it is difficult to assess the efficacy and effects of Canadian anti-trafficking laws and policies due to the institutional and political limitations to collecting legal data in this highly politicised subject area. They conclude with five recommendations to increase the transparency of Canada’s public claims about its anti-trafficking enforcement efforts and call for more empirically-based law reform.